Menggali Tantangan Motivasi dan Kesenjangan Minat Siswa: Studi Kasus Pembelajaran PPKN di SMP Negeri 35 Medan - Ulfa Fatimah; Elsa Prida Br Tarigan; Alya Rachma; Ameliya Harahap; Erbina Br Sembiring; Liber Siagian; Fazli Rachman (Universitas Muhammadiyah Enrekang, 2023)
Education is considered as the main investment for the future of the nation, with motivation to learn as the key to success inthe educational process. In the context of learning in SMP Negeri 35 Medan, the main challenges faced are lack of motivationand gaps in student learning interests. This study uses descriptive qualitative research methods. A monotonous and lessinteractive learning process, it often involves learning methods that tend to memorize and are less attractive to students. Inaddition, inadequate facilities and network access are also an obstacle. The results showed that students tend to be bored andless motivated when studying. Teachers at SMP Negeri 35 still often use traditional methods that emphasize memorizationrather than active student interaction. To overcome this problem, a more inspiring and interactive learning approach is needed,as well as the use of more interesting learning media. Teachers also need to be more proactive in communicating with students and creating an environment that supports students ' motivation and interest in learning. These efforts are expected to improve the quality of learning and learning outcomes of students in SMP Negeri 35 Medan.